2021
DOI: 10.1038/s41598-021-97176-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-specific deletion of β-catenin protects mouse hearts from ventricular arrhythmias after myocardial infarction

Abstract: Wnt/β-catenin signaling is activated in the heart after myocardial infarction (MI). This study aims to investigate if β-catenin deletion affects post-MI ion channel gene alterations and ventricular tachycardias (VT). MI was induced by permanent ligation of left anterior descending artery in wild-type (WT) and cardiomyocyte-specific β-catenin knockout (KO) mice. KO mice showed reduced susceptibility to VT (18% vs. 77% in WT) at 8 weeks after MI, associated with reduced scar size and attenuated chamber dilation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…182,183 Interestingly, βcatenin deletion is also cardioprotective and reduces susceptibility to arrhythmias after myocardial infarction, likely through the attenuation of structural remodeling. 184 Proper βcatenin cascade activity maintains the resident CPC population in the adult heart. 142 The prolonged stabilization of βcatenin, starting from late embryogenesis, aggravates myocardial infarction and enhances mortality by impairing the differentiation of resident CPCs.…”
Section: Canonical Wnt Pathway In Postnatal Heart Growth and Heart Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…182,183 Interestingly, βcatenin deletion is also cardioprotective and reduces susceptibility to arrhythmias after myocardial infarction, likely through the attenuation of structural remodeling. 184 Proper βcatenin cascade activity maintains the resident CPC population in the adult heart. 142 The prolonged stabilization of βcatenin, starting from late embryogenesis, aggravates myocardial infarction and enhances mortality by impairing the differentiation of resident CPCs.…”
Section: Canonical Wnt Pathway In Postnatal Heart Growth and Heart Re...mentioning
confidence: 99%
“…Inducible cardiac‐specific GSK3β deletion also improves heart healing after infarction and limits heart dilatation 182,183 . Interestingly, β‐catenin deletion is also cardioprotective and reduces susceptibility to arrhythmias after myocardial infarction, likely through the attenuation of structural remodeling 184 …”
Section: β‐Catenin In Cardiogenesis Postnatal Heart Growth and Cardia...mentioning
confidence: 99%
“…The inhibition of Nav1.5 by Wnt/β-catenin is responsible for arrhythmia in the acute phase after MI, while the mechanism of arrhythmia in the chronic phase after MI is more likely to involve myocardial remodeling rather than changes in ion channels. Jerry Wang et al ( Wang J. et al, 2021 ) observed a reduction in the occurrence of arrhythmias in β-catenin-knockout (KO) mice at 8 weeks after MI, which was consistent with reduced scar size and ventricular dilation, and Na + /K + channel genes were not different between WT (wild type) and KO mice ( Wang J. et al, 2021 ).…”
Section: β-Catenin and Cardiac Diseasesmentioning
confidence: 83%
“…Wnt/β-catenin signaling which plays an important role in development of the heart [ 38 ]. Wnt signaling has been shown to be re-activated in the ischemic myocardium, both in the infarct and peri-infarct areas [ 39 , 40 ]. Renin-angiotensin system activation also leads to activation of Wnt signaling/β-catenin signaling [ 41 ].…”
Section: Discussionmentioning
confidence: 99%